Highjump. Improve your technique from novice to international level - Reid, P. (Modern Athlete & Coach, 2014)
The article discusses how to improve techniques for high jump, from novice to international level of jumping performance. It offers information on a mini trampoline approach, the most effective jumping technique for high jumpers. It outlines the division of concentration points of jumpers during training, the propulsion, and the directional components